The impact of COVID-19 vaccines on fertility-A systematic review and meta-analysis. Issue 42 (6th October 2022) - Zaçe, D.; La Gatta, E.; Petrella, L.; Di Pietro, M.L.
Highlights: Vaccination against SARS-CoV-2 remains an important measure to prevent serious infection. Misinformation and doubts regarding the vaccines should be properly addressed. Studies published so far report no association between covid19 vaccines and fertility. Future studies should focus on longer follow up time, systematic investigation, and representativeness. Abstract: Background: Despite literature's evidence about COVID-19 vaccines' safety, concerns have arisen regarding adverse events, including the possible impact on fertility, accentuated by misinformation and anti-vaccine campaigns. The present study aims to answer the question: Is there any impact of COVID-19 vaccines on the fertility of men and women of reproductive age? Methods: PubMed, Scopus, Web of Science, Cochrane and Embase databases were searched for eligible studies until June 8th, 2022. The search was restricted to articles regarding humans, published in any languages, without additional restrictions. Studies' quality was assessed by the Newcastle-Ottawa and the Before and After Quality Assessment scales for cohort and pre-post studies, respectively. Random-effect meta -analyses were performed for parameters considered in ≥ 2 studies, calculating means, p -values and 95 % Confidence Intervals (CIs). Results: Out of 1406 studies screened, 29 were included in the systematic review. These studies, conducted in Israel (34.5 %), USA (24.1 %), Russia (20.7 %) China (10.3 %), Italy (3.5 %), North America (3.5%) and Turkey (3.5 %) were of poor (34.5 %), moderate (58.6 %) and good (6.9 %) quality. Meta-analyses were performed for pre- and post-vaccination sperm progressive motility (44 %, 95 % CI 42 %-62 % vs 43 %, 95 % CI 31 %-59 % p = 0.07) and concentration (50.6 mln/ml, 95 % CI 35.1–72.8 vs 55.4 mln/ml, 95 % CI 37.4–82.2p = 0.12). Biochemical (0.51, 95 % CI 0.40–0.66 vs 0.60, 95 % CI 0.53–0.68p = 0.45) and clinical (0.45, 95 % CI 0.37–0.54 vs 0.47, 95 % CI 0.40–0.55 p = 0.31) pregnancy rate did not differ among vaccinated and not vaccinated groups. Subgroup meta -analyses based on the type of vaccine showed no significant difference: between vaccinated with mRNA vaccines and non-vaccinated regarding biochemical pregnancy rates; pre- and post-vaccination with Gam-COVID-Vac regarding testosterone, FSH and LH levels; pre- and post-vaccination with BNT162b2 vaccines regarding sperm volumes. Conclusion: Based on the studies published so far, there is no scientific proof of any association between COVID-19 vaccines and fertility impairment in men or women.